The family : three fates in the twentieth century - Laskin, David, 1953- (Viking, 2013)
Traces the history of the 20th century through the story of an extraordinary Jewish family, recounting how the author's 19th-century ancestors were separated by period upheavals in western Russia and went on to become the founders of the Maidenform Bra Company, pioneers in the contentious birth of Israel, and victims of the Holocaust.